2017
DOI: 10.1111/hel.12430
|View full text |Cite
|
Sign up to set email alerts
|

Protective efficacy of a hydroxy fatty acid against gastric Helicobacter infections

Abstract: HYA prevents gastric Helicobacter infections by blocking their futalosine pathways. Daily HYA supplementation is effective for the prevention of gastric mucosa-associated lymphoid tissue lymphoma induced by persistent infection with H. suis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…A mixture of 10-HFAs was patented as an intestinal tract protecting agent [22] while 10-hydroxystearic acid proved to ameliorate skin age spots and conspicuous pores [23]. Fatty acid esters of 13-hydroxy linoleic acid are anti-inflammatory [24]: 9-hydroxystearic acid (9-HSA) shows anticancer properties [25] whereas (12Z)-10-hydroxy-octadecenoic acid possesses antifungal properties [26] and is able to prevent gastric Helicobacter infections by blocking their futalosine pathways [27]. In addition, recent studies have demonstrated that HFAs produced by human gut bacteria play a relevant role in the control of allergy, inflammation, and immunity, pointing to the involvement of their metabolites in the so-called gut-skin axis [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…A mixture of 10-HFAs was patented as an intestinal tract protecting agent [22] while 10-hydroxystearic acid proved to ameliorate skin age spots and conspicuous pores [23]. Fatty acid esters of 13-hydroxy linoleic acid are anti-inflammatory [24]: 9-hydroxystearic acid (9-HSA) shows anticancer properties [25] whereas (12Z)-10-hydroxy-octadecenoic acid possesses antifungal properties [26] and is able to prevent gastric Helicobacter infections by blocking their futalosine pathways [27]. In addition, recent studies have demonstrated that HFAs produced by human gut bacteria play a relevant role in the control of allergy, inflammation, and immunity, pointing to the involvement of their metabolites in the so-called gut-skin axis [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…A number of free fatty acids (FFAs), with potent antibacterial activities against a broad range of bacteria (18)(19)(20)(21), including H. pylori, are of considerable research interests. In particular, FFAs seem to induce no acquired resistance to the antibacterial effect and are considered safe, which make them attractive as antibacterial agents for commercial exploitation.…”
mentioning
confidence: 99%
“…plantarum into dairy products could lead to the production of such a therapeutic agent. Recently, the antimicrobial activity of HYA has been reported against Helicobacter pylori (Matsui et al., 2017). There is no study on the antibacterial effects of HYA against foodborne pathogens and spoilage microorganisms.…”
Section: Food Applications Of Postbioticsmentioning
confidence: 99%